Dynamics of exotic species and their establishment in the Pawnee National Grasslands - Lauenroth, William K., author; Betz, Dani-Ella, author; SGS-LTER, Colorado State University, publisher (Colorado State University. Libraries, 2000)
We investigated the distribution of plant species in the shortgrass steppe to determine if the roadsides were acting as corridors, increasing the susceptibility of the open steppe to exotic species establishment. We surveyed 45 paired roadside and open steppe sites and found few exotic species in the the open steppe (.36/m2), whereas the roadsides contained significantly more (5.42/m2). We examined the soil seed bank along a transect from roadsides to 25 meters into the open steppe to investigate the range of seed dispersal and abundance of roadside exotic seeds. We found that a significantly greater number of exotic seeds in the roadsides (873 seeds per m2) versus the open steppe (109 seeds per m2). To investigate the dynamics of exotic species establishment we planted two exotic species, downy brome (Bromus tectorum) and Dalmation toadflax (Linaria dalmatica), into the open steppe. A matrix of 5 treatments was applied and after one field season Bromus tectorum germinated and established in many plots. The nitrogen and nitrogen plus water treatments were the most successful in promoting the growth of Bromus. Linaria dalmatica did not establish in any of the research plots. The open steppe has few exotic species and we found that few exotic seeds exist in the seed bank. Furthermore, our work indicates that even if exotic species seeds were numerous, they may have difficulty germinating and establishing in the native communities.
The SGS-LTER research site was established in 1980 by researchers at Colorado State University as part of a network of long-term research sites within the US LTER Network, supported by the National Science Foundation. Scientists within the Natural Resource Ecology Lab, Department of Forest and Rangeland Stewardship, Department of Soil and Crop Sciences, and Biology Department at CSU, California State Fullerton, USDA Agricultural Research Service, University of Northern Colorado, and the University of Wyoming, among others, have contributed to our understanding of the structure and functions of the shortgrass steppe and other diverse ecosystems across the network while maintaining a common mission and sharing expertise, data and infrastructure.
Colorado State University. Natural Resource Ecology Laboratory; Colorado State University. Department of Forest and Rangeland Stewardship; Colorado State University. Department of Soil and Crop Sciences; Colorado State University. Department of Biology; California State University, Fullerton; United States. Agricultural Research Service; University of Northern Colorado.
Keywords: long term ecological research; grassland ecology; shortgrass steppe; Central Plains Experimental Range; Pawnee National Grassland